Single-Use vs Reuse: Unit Cost Analysis of Hemodialysis with Activity-Based Costing and Double Distribution - Saptari, Dhany; Ramadhan, Yanuar; Hilmy, Mohamad Reza (Riviera Publishing, 2025)
Hemodialysis is a vital therapy for chronic kidney failure patients, yet accurate unit cost calculation remains a challenge for hospitals under the National Health Insurance (JKN) system. This study aims to analyze the unit cost calculation of outpatient hemodialysis procedures at a private hospital in Indonesia using Activity-Based Costing (ABC) and Double Distribution (DD) methods, and to compare them with INA-CBGs tariffs to evaluate potential financial losses and formulate efficiency strategies. This descriptive observational study with a quantitative approach used 350 samples of BPJS hemodialysis procedures from January-March 2023. Data were obtained through service flow observations, clinical and financial documentation, and interviews with relevant stakeholders, validated by the hospital's finance department. Results show that ABC method unit costs (Rp1,102,848 for reuse and Rp1,197,184 for single-use) are higher than DD (Rp948,756 for reuse and Rp1,043,092 for single-use), with ABC considered more accurate as it reflects real resource consumption. Both methods show unit costs exceeding INA-CBGs tariffs (Rp800,360 for reuse and Rp941,600 for single-use), indicating potential annual financial losses of Rp142-423 million. Clinical pathway-based efficiency strategies are needed to achieve cost control while maintaining care quality, with recommendations to adopt single-use dialyzers as operational standards to improve patient safety and reduce long-term financial risks.